2022
DOI: 10.3389/fnut.2022.1003545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein score and carbohydrate quality index with the risk of chronic kidney disease: Findings from a prospective cohort study

Abstract: Background/AimThis study aimed to examine the associations between dietary protein score and carbohydrate quality index (CQI) and the risk of chronic kidney disease (CKD) in Iranian adults.MethodsThis population-based cohort study was performed within the Tehran Lipid and Glucose Study framework on 6,044 subjects aged ≥18 years old, who were followed up for a mean of 7.7 years. Dietary protein score and CQI were determined using a food frequency questionnaire. CKD was defined as an estimated glomerular filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Few large observational studies have examined the associations of carbohydrate types and sources with the risk of CKD, and none have focused on specific sugar types in detail. 6,8 The findings of our study suggested that the intake of specific types of sugars may have diverging associations with CKD risk. We found that the consumption of free sugar was positively associated with incident CKD; whereas regarding non-free sugar intake, there was an inverse association.…”
Section: Papermentioning
confidence: 73%
See 1 more Smart Citation
“…Few large observational studies have examined the associations of carbohydrate types and sources with the risk of CKD, and none have focused on specific sugar types in detail. 6,8 The findings of our study suggested that the intake of specific types of sugars may have diverging associations with CKD risk. We found that the consumption of free sugar was positively associated with incident CKD; whereas regarding non-free sugar intake, there was an inverse association.…”
Section: Papermentioning
confidence: 73%
“…Emerging nutritional epidemiological studies have explored the potential role of dietary carbohydrates in CKD risk and have increasingly suggested that the current focus on carbohydrate quantity should shift toward carbohydrate types or sources to obtain a greater benefit for CKD prevention. [6][7][8] As important forms of carbohydrates, free sugars (all monosaccharides and disaccharides added to foods by the manufac-turer, cook, or consumer, plus sugars naturally present in honey, syrups, and unsweetened fruit juices) and non-free sugars (all sugars excluded from the definition of free sugars, mostly naturally occurring in fruit, vegetables, and dairy products) have garnered increasing attention from various public health organizations that advocate for limiting free sugars for additional health benefits. 9,10 A large body of evidence has linked the intake of sugar-sweetened beverages (SSBs), the major source of free sugars, with a greater risk of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, with the sum of the scores of these two items, people get a score between 0 and 20, which is the higher score indicating a higher relative consumption of protein or higher PAR. For this purpose, the index components are also reported separately [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a novel protein score has been introduced to assess the quality and quantity of dietary protein intake, which combines both total protein and the plant-to-animal ratio (PAR) [ 15 ]. Although some studies may have shown the possible role of protein score in predicting the risk of chronic diseases [ 16 ], no study has yet examined the association between the dietary protein score and the risk of MetS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation